Words of passage : national longing and the imagined lives of Mexican migrants - Dick, Hilary Parsons (University of Texas Press, 2018)
Migration fundamentally shapes the processes of national belonging and socioeconomic mobility in Mexico--even for people who never migrate or who return home permanently. Discourse about migrants, both at the governmental level and among ordinary Mexicans as they envision their own or others' lives in "El Norte," generates generic images of migrants that range from hardworking family people to dangerous lawbreakers. These imagined lives have real consequences, however, because they help to determine who can claim the resources that facilitate economic mobility, which range from state-sponsored development programs to income earned in the North. Words of Passage is the first full-length ethnography that examines the impact of migration from the perspective of people whose lives are affected by migration, but who do not themselves migrate. Hilary Parsons Dick situates her study in the small industrial city of Uriangato, in the state of Guanajuato. She analyzes the discourse that circulates in the community, from state-level pronouncements about what makes a "proper" Mexican to working-class people's talk about migration. Dick shows how this migration discourse reflects upon and orders social worlds long before--and even without--actual movements beyond Mexico. As she listens to men and women trying to position themselves within the migration discourse and claim their rights as "proper" Mexicans, she demonstrates that migration is not the result of the failure of the Mexican state but rather an essential part of nation-state building